PENGARUH KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KINERJA PEGAWAI - Sulan Junawar; Patwayati Patwayati; Endro Sukotjo; Nursaban Rommy (Pascasarjana Universitas Halu Oleo, 2017)
This study aims to examine and analyze empirically the influence of organizational commitment on organizational citizenship behavior (OCB) and employee performance at the Office of EducationThe results showed that (1) Organizational commitment directly had a positive and significant effect on organizational citizenship behavior. The better organizational commitment, the higher organizational citizenship behavior of Kolaka District Education, Youth and Sports Office employees. (2) Organizational commitment directly has a positive and significant effect on employee performance. (3) Organizational citizenship behavior directly has a positive and significant effect on employee performance. (4) Organizational commitment indirectly affects employee performance through organizational citizenship behavior Keywords:Organizational Commitment, Organizational Citizenship Behavior (OCB) and Employee Performance